Duong Tuong’s dialect translation strategies of Joseph’s speech in “Wuthering heights” by Emily Bronte = Chiến lược dịch tiếng địa phương được Dương Tường áp dụng đối với lời thoại của nhân vật Joseph trong tiểu thuyết đồi gió hú (Emily Bronte) - Nguyễn, Hà My (2021)
English Literature Translation always draws attention from students of English as a second language and from translators who are major in Linguistics. And dialect translation has been also noticed more attention from translators in recent time. In this research, the translation of dialect in the novel Wuthering Heights by Emily Bronte will be studied based on Duong Tuong translation’s version. The purposes of this research is figuring out the applied strategies and the most dominant one to render dialect words spoken by Joseph in the novel. 116 dialect words in 32 speeches were chosen as the cases of this study. These words were categorized into three groups: Lexical dialect, Phonological dialect and Grammar dialect. After that, the researcher investigated how Duong Tuong translated dialect in this novel and figured out three strategies: Lexicalization, Partial and Relativization. Given the analysis of data, the calculation was made to draw out the most preferable translation strategy which is Lexicalization. For further studies, the related topics are open to many other researchers in the combination of the strategies and the expansion of the scope of this study.